Prevalence and multilocus genotyping of Giardia duodenalis in Holstein cattle in Yunnan, China - Heng, Zhao-Jun; Yang, Jian-Fa; Xie, Xin-Yan; Xu, Cui-Rong; Chen, Jun-Rong; Ma, Jun; He, Jun-Jun; Mao, Hua-Ming (Frontiers in Veterinary Science, 2022)
Giardia duodenalis is an important zoonotic protozoa, which can infect a variety of animals, causing diarrhea and even death of animals or human. Dairy cattle have been implicated as important sources of human G. duodenalis. However, the information about the prevalence and genetic diversity of G. duodenalis in dairy cattle in China's Yunnan Province remains limited. This study investigated the occurrence and multilocus genotyping of G. duodenalis of Holstein cattle in Yunnan Province, China. A total of 524 fresh fecal samples were randomly collected from Holstein cattle in 8 farms in Yunnan. In this study, 27.5% (144/524) tested samples were positive for G. duodenalis infection. The highest infection ratio was found in pre-weaned calves (33.7%), and the infection rates of post-weaned calves, growing cattle and adult cattle were 24.5%, 23.0% and 17.3%, respectively. Sequence analysis of the SSU rRNA gene showed that the predominant assemblage of G. duodenalis in this study was assemblage E (97.9%, 141/144), whereas assemblage A was identified only in three samples (2.1%, 3/144). All G. duodenalis positive samples were further assayed with nested PCR targeting β-giardin (bg), triosephosphate isomerase (tpi) and glutamate dehydrogenase (gdh) genes, and 87, 41 and 81 sequences were obtained, respectively. The presence of mixed infection by both assemblage A and E of G. duodenalis was detected in three sample. Multilocus genotyping yielded 23 multilocus genotypes (MLGs). The present study reveals (for the first time) the prevalence data of G. duodenalis in Holstein cattle in Yunnan Province, which provided baseline data for the prevention and control of G. duodenalis infection in Holstein cattle in Yunnan Province, China.